PERBANDINGAN HUKUM TENTANG HAK ANAK LUAR KAWIN DALAM HAL PEWARISAN DITINJAU BERDASARKAN UNDANG-UNDANG NO 1 TAHUN 1974 TENTANG PERKAWINAN DAN KITAB UNDANG-UNDANG HUKUM PERDATA PASCA KELUARNYA PUTUSAN MAHKAMAH KONSTITUSI NO 46/PUU-VIII/2010 - Sylvia Pratiwi Limbong; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
considers marriage only of civil relations. That the rights of the child outside of marriage in terms of inheritance in the Civil Code subject to the provisions of Article 863 of the Civil Code which meenyatakan that, the child outside marriage that has been recognized as having the right to inherit to the biological parents even with the inheritance that is not the same with children other legitimate.The right of a child outside marriage in terms of inheritance in the UUP UUP provided for in Article 42 which states that, the position of a new child is considered valid if born of a lawful marriage, so if there is a child born outside marriage is not valid by law (for example, a child is born only of marriage siri or born outside of marriage).That the comparison of the rights of children outside marriage in terms of inheritance are reviewed by the Civil Code is the shape of the validity of a child in the form of a birth certificate , while in the post- keluarmya UUP Court Decision No. 46 / PUU - VIII / 2010 the validity of a child outside of marriage can be proved by science and technology and / or other evidence under the law to have a blood relationship , including a civil relationship with his father's family , for example by doing a DNA test.Marriage Certificate which should be owned by married couples did not exist, because the marriage is not recorded. In July 2010, Machica Mochtar struggled through the Constitutional Court to obtain recognition of the legal status of Iqbal as a legitimate child. Machica considers that Article 2 paragraph (2) regarding the registration of marriage, has hurt the status of his son, who was born of the marriage that is not recorded, as well as Article 43 paragraph (1), blocking Iqbal has a civil relationship with Moerdiono.The existence of this decision, of course, have an impact on the legal order of marriage in Indonesia, particularly regarding the position of a child outside marriage. Investigate further the consideration of the judges of the Constitutional Mahkmah in taking such decisions as well as well as analyzing Article 43 paragraph (1) after the decision of the Constitutional Court is the review of the Code of Civil Code.Keywords : Marriage - Child Outside Marriage – Inheritance